Combustion Characteristics of Methane Hydrate Flames - Yu-Chien Chien; Derek Dunn-Rankin (Energies, 2019)
This research studies the structure of flames that use laboratory-produced methane hydrates as fuel, specifically for the purpose of identifying their key combustion characteristics. Combustion of a methane hydrate involves multiple phase changes, as large quantities of solid clathrate transform into fuel gas, water vapor, and liquid water during burning. With its unique and stable fuel energy storage capability, studies in combustion are focused on the potential usage of hydrates as an alternative fuel source or on their fire safety. Considering methane hydrate as a conventional combustion energy resource and studying hydrate combustion using canonical experimental configurations or methodology are challenges. This paper presents methane hydrate flame geometries from the time they can be ignited through their extinguishment. Ignition and burning behavior depend on the hydrate initial temperature and whether the clathrates are chunks or monolithic shapes. These behaviors are the subject of this research. Physical properties that affect methane hydrate in burning can include packing density, clathrate fraction, and surface area. Each of these modifies the time or the temperature needed to ignite the hydrate flames as well as their subsequent burning rate, thus every effort is made to keep consistent samples. Visualization methods used in combustion help identify flame characteristics, including pure flame images that give reaction zone size and shape and hydrate flame spectra to identify important species. The results help describe links between hydrate fuel characteristics and their resulting flames.